Neurocardiogenic syncope: a rare presentation of pharyngeal lymphoma. (9th November 2012) - Li, Anthony; Bandali, Alykhan; Ghani, Saqib; Reid, Colin
Abstract : Syncope is a common symptom of patients attending emergency departments, yet presents significant diagnostic and therapeutic challenges. We present a rare cause of recurrent vasovagal syncope with predominant cardioinhibitory response due to lymphoma surrounding and compressing the carotid artery treated successfully with radiotherapy.